2022
DOI: 10.1101/gr.277067.122
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation inC. elegansshort tandem repeats

Abstract: Short tandem repeats (STRs) represent an important class of genetic variation that can contribute to phenotypic differences. Although millions of single nucleotide variants (SNVs) and short indels have been identified among wild Caenorhabditis elegans strains, the natural diversity in STRs remains unknown. Here, we characterized the distribution of 31,991 STRs with motif lengths of 1-6 bp in the reference genome of C. elegans. Of these STRs, 27,667 harbored polymorphisms across 540 wild strains and only 9,691 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 69 publications
(159 reference statements)
2
22
0
Order By: Relevance
“…3a ), our result is consistent with the observation that N2 and PB306 genotypes show similar mutation rates and molecular spectra for single nucleotide polymorphisms ( Denver et al 2012 ; Rajaei et al 2021 ). However, a more recent study with an extensive set of MA lines from both genotypes has indicated that mutation rates for short-tandem repeats (STRs) were different ( Zhang et al 2022 ). Given that some of these STRs have also been shown to affect QTL for polygenic traits ( Zhang et al 2022 ), one could have expected that the two M matrices for locomotion behavior would be different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3a ), our result is consistent with the observation that N2 and PB306 genotypes show similar mutation rates and molecular spectra for single nucleotide polymorphisms ( Denver et al 2012 ; Rajaei et al 2021 ). However, a more recent study with an extensive set of MA lines from both genotypes has indicated that mutation rates for short-tandem repeats (STRs) were different ( Zhang et al 2022 ). Given that some of these STRs have also been shown to affect QTL for polygenic traits ( Zhang et al 2022 ), one could have expected that the two M matrices for locomotion behavior would be different.…”
Section: Discussionmentioning
confidence: 99%
“…However, a more recent study with an extensive set of MA lines from both genotypes has indicated that mutation rates for short-tandem repeats (STRs) were different ( Zhang et al 2022 ). Given that some of these STRs have also been shown to affect QTL for polygenic traits ( Zhang et al 2022 ), one could have expected that the two M matrices for locomotion behavior would be different. Regarding M matrix orientation, it should depend on pleiotropy and therefore on the amount of genetic covariances between transition rates ( Lande 1980 ; Phillips and McGuigan 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…No obvious homology is observed around the breakpoints of the sprDf1 allele, suggesting that the microdeletion allele may not have arisen by this classic mechanism. However, extended microsatellite repeat sequences are located within a few hundred base pairs of both breakpoint sites [54]. An extended octonucleotide repeat sequence ATGCCTAC is found in 27 copies upstream of the left breakpoint, and 26 copies of a hexanucleotide repeat sequence CTAAGC are found upstream of the right breakpoint.…”
Section: How Did the Microdeletion Allele Arise?mentioning
confidence: 99%
“…Variation in the length of short tandem repeats is associated with diverse phenotypic changes across organisms [6][7][8][9][10][11] . In humans, extreme length variants exemplified by repeat expansions cause several diseases such as Huntington's disease and Friedreich's ataxia 8,12 .…”
mentioning
confidence: 99%
“…AL3 physically interacts with LHP1 of the PRC1 complex and the FUG1-AL3-LHP1 module is essential to confer repeat expansion-associated epigenetic silencing. Our findings highlight the importance post-translational modifiers and histone readers in epigenetic silencing caused by repeat expansions.Variation in the length of short tandem repeats is associated with diverse phenotypic changes across organisms [6][7][8][9][10][11] . In humans, extreme length variants exemplified by repeat expansions cause several diseases such as Huntington's disease and Friedreich's ataxia 8,12 .…”
mentioning
confidence: 99%